China's Response to the Expansion of U.S. Influence in Asia: The Intersection of Religion and Governance in Afghanistan (2011-2019) - Paryani, Nazari; Rahmany, Gulab Mir (FISIP UIN Sunan Gunung Djati Bandung, 2024)
Research Problem: The article addresses China’s concerns regarding the expansion of U.S. influence in Asia, particularly focusing on Afghanistan's strategic importance in the geopolitical competition between the two powers. The U.S. military presence and Afghanistan’s religiously influenced governance pose a significant challenge for China, which must navigate both political and religious dynamics to secure its interests in the region. This research investigates how these factors shape China’s foreign policy and its interactions with Afghanistan. Research purposes: The study aims to explore how China’s foreign policy towards Afghanistan has evolved in response to the geopolitical and religious landscape influenced by U.S. actions. Specifically, it examines China’s strategic calculations regarding Afghanistan’s religious governance and how this affects its efforts to engage with Afghan political actors, such as the Taliban, while maintaining its broader geopolitical and economic goals, including the Belt and Road Initiative. Research methods: The research employs a historical and analytical approach, drawing on data from 2011 to 2019 to examine China's foreign policy shifts in response to U.S. actions in Afghanistan. The study relies on secondary sources, including policy papers, academic works, and governmental reports, to assess China’s evolving role and strategies concerning the religiously influenced political structures in Afghanistan. Results and Discussion: The findings show that China’s foreign policy towards Afghanistan is significantly influenced by its concerns over U.S. military presence and alliances in the region. China’s engagement with Afghanistan has been shaped by the need to navigate the religious-political dynamics, particularly with the rise of religiously motivated actors such as the Taliban. China’s strategic responses include strengthening diplomatic ties, economic investments, and engaging with both Afghan religious and political leaders to secure its geopolitical interests. The article discusses how China's secular approach to governance contrasts with Afghanistan’s religious influences, affecting its foreign policy strategies. Research Implications and Contributions: This study contributes to the broader understanding of how religion, politics, and governance intersect in Afghanistan’s international relations, particularly with China. It provides insights into how China adapts its foreign policy to account for religiously motivated governance, while also pursuing its geopolitical goals in the region. The research offers valuable perspectives for policymakers and scholars on the interplay between religion, governance, and foreign policy in a strategically significant context like Afghanistan.